2010
DOI: 10.1007/s11914-010-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of FSH and TSH in Bone Loss and Its Clinical Relevance

Abstract: Osteoporosis, a global health problem, is now frequently recognized to be secondary to alterations in the pituitary-bone axis. This review examines the current evidence for how dysregulation of the pituitary-bone axis leads to osteoporotic bone loss. Specifically, perimenopausal bone loss in the context of follicle-stimulating hormone action, and hyperthyroid bone loss in the context of thyroid-stimulating hormone action are explored. From the reviewed scientific findings, recommendations for early diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
(81 reference statements)
0
10
0
1
Order By: Relevance
“…Iqbal et al reported that FSH increases TNF-α production in immune cells, stimulates the formation of osteoclasts and bone absorption and modifies bone mass independently of serum estrogen levels [ 29 , 30 , 31 ]. Short-term treatment with FSH and hCG altered signaling pathways involved in mesenchymal stem cell (MSC) proliferation, including Erk1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Iqbal et al reported that FSH increases TNF-α production in immune cells, stimulates the formation of osteoclasts and bone absorption and modifies bone mass independently of serum estrogen levels [ 29 , 30 , 31 ]. Short-term treatment with FSH and hCG altered signaling pathways involved in mesenchymal stem cell (MSC) proliferation, including Erk1/2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the growth hormone is associated with that of the thyroid hormones, which increase the energy production in all cells of the body and influence positively the growth of the skeleton [10]. It is also associated with the pituitary hormone thyrotropin, which stimulates the thyroid hormones, which may have direct effects on bone [11].…”
Section: Bone Modelingmentioning
confidence: 99%
“…The occurrence of bone loss in late perimenopause, before estrogen levels decline, prompted an investigation of whether FSH may impact bone metabolism [71]. The effects of FSH on BMD are not fully known.…”
Section: Possible Role Of Other Hormonesmentioning
confidence: 99%